2017
DOI: 10.1186/s40461-017-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Vocational learning in a Swedish post-secondary apprenticeship

Abstract: Background: In Sweden, some occupations require post-secondary apprenticeship, e.g. those who are to become construction workers, while some do not, e.g. those who are to become business and administration workers. Research on post-secondary apprenticeship can be regarded as sparse. To address vocational learning in post-secondary apprenticeship, this explorative study focuses on apprentices in the construction industry. The aim of this study is to identify how vocational learning is constituted within workpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Unwin's (2003, 2004) models of 'expansive' workplace learning mention favourably 'managers as facilitators of workforce and individual development' (2004, 130) rather than high-status trainers. The contributions of trainers can prove ephemeral even in countries where workplace learning is more effectively integrated within TVET (Nägele and Neuenschwander 2016), especially in apprenticeships, which centre on learning from experienced workers (Fjellström 2017). Winch (2000) argued that narrow definitions had been used to describe training as simply the process of cognition: more complex understandings would include a gradual acquisition of expertise, the interpenetration of knowledge and skills, an ability to apply them to fresh situations and a relationship with foundational knowledge.…”
Section: Vocational Educators Professionality and Changementioning
confidence: 99%
“…Unwin's (2003, 2004) models of 'expansive' workplace learning mention favourably 'managers as facilitators of workforce and individual development' (2004, 130) rather than high-status trainers. The contributions of trainers can prove ephemeral even in countries where workplace learning is more effectively integrated within TVET (Nägele and Neuenschwander 2016), especially in apprenticeships, which centre on learning from experienced workers (Fjellström 2017). Winch (2000) argued that narrow definitions had been used to describe training as simply the process of cognition: more complex understandings would include a gradual acquisition of expertise, the interpenetration of knowledge and skills, an ability to apply them to fresh situations and a relationship with foundational knowledge.…”
Section: Vocational Educators Professionality and Changementioning
confidence: 99%
“…These raises concerns that the survey results show that vocational graduates are not ready for the industrial world because of the large number of unemployed in the data shown. The obstacles faced by students in career planning are largely caused by a lack of knowledge regarding job information and limited understanding regarding individual interests and potential (Fjellström, 2017) (Schmid & Haukedal, 2022). As a result, it seems that students generally do not understand the steps they need to take to build their careers.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars across different disciplines including HRD (Alagaraja & Githens, 2016), labour studies (Barrett et al., 2013), VET (Fjellström, 2017) and economics (Fitzenberger & Volter, 2007) have studied the NHRD phenomenon, and individually these investigations provide important insights into NHRD as a concept. Beyond their interest in the NHRD phenomenon, these diverse literatures share both confidence in, and enthusiasm for, the effectiveness of NHRD.…”
Section: Introductionmentioning
confidence: 99%